The function of the myth in Plato - Menezes, Luiz Maurício Bentim da Rocha (Argumentos - Revista de Filosofia, 2018)
The work that we propose on the study of the myth in the work of Plato is based on the article of Ludwig Edelstein titled “The Function of the Myth in Plato’s Philosophy”. In his work, Edelstein presents to us, in a general way, the reason why Plato uses the myth and the function it plays in his philosophy. The author thus contributes to the development of thought on the subject and provides a lever for later studies on the myth in Plato. Finally, we will come to a critical conclusion on the subject.